2014
DOI: 10.1049/iet-sen.2013.0190
|View full text |Cite
|
Sign up to set email alerts
|

Case study on risk management practice in large offshore‐outsourced Agile software projects

Abstract: Information systems, offshoring and outsourcing have resulted in significant changes to software engineering practices. In this study, the authors explore industry practices in risk management in a large offshore-outsourced Agile Scrum software development project. The project consisted of distributed teams from two different IT vendors. Agile method is suitable for small and collocated teams, where the team members have high level of knowledge and commitment. In this study, the authors explore the challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 15 publications
0
49
0
3
Order By: Relevance
“…Similarly, an independent observer (e.g., a matched pair survey conducted on both sides, client and vendor) reporting about projects instead of self-administered questionnaires for data gathering would further minimize social desirability bias. As we did not ask specifically for the usage of agile development practices, future research might also investigate the role of communication in agile versus non-agile projects, since agile development practices often rely on a high level of communication and face-to-face meetings (Inayat, Salim, Marczak, Daneva, & Shamshirband, 2015;Khan & Khan, 2013;Sundararajan, Bhasi, & Vijayaraghavan, 2014). As indicated by our results, this might lead to further insights regarding CVC as well as process and product satisfaction.…”
Section: Implications For Researchmentioning
confidence: 90%
“…Similarly, an independent observer (e.g., a matched pair survey conducted on both sides, client and vendor) reporting about projects instead of self-administered questionnaires for data gathering would further minimize social desirability bias. As we did not ask specifically for the usage of agile development practices, future research might also investigate the role of communication in agile versus non-agile projects, since agile development practices often rely on a high level of communication and face-to-face meetings (Inayat, Salim, Marczak, Daneva, & Shamshirband, 2015;Khan & Khan, 2013;Sundararajan, Bhasi, & Vijayaraghavan, 2014). As indicated by our results, this might lead to further insights regarding CVC as well as process and product satisfaction.…”
Section: Implications For Researchmentioning
confidence: 90%
“…These were also cited by Shrivastava and Rathod . Moreover, Sundararajan et al and Ramesh et al identified some additional challenges, including the lack of communication effectiveness, lack of roles and responsibilities among the team members, inappropriate technology selection, lack of customer involvement, large team sizes, lack of effective communication, and lack of trust between the client and vendor organizations, all of which have been experienced by the practitioners in distributed agile development …”
Section: Literature Reviewmentioning
confidence: 99%
“…Willingness to provide information and share knowledge [20] • (Having) Good communication [5] Resolution: Increased communication leads to increased trust [5] sing face-to-face communication -as much as possible -to develop trust [38] Prerequisite: Improved communication as a result of trust [20] Table 4 is similar to Table 3 in all aspects but with a focus on how to maintain a regular pace of communication and collaboration within Agile teams. The same is true for Table 5 which addresses ways to improve communication by using tools and methods that facilitate and simplify it.…”
Section: Trust Categorymentioning
confidence: 99%